Surveillance After Snowden - Lyon, David (Polity, 2015)
In 2013, Edward Snowden revealed that the NSA and its partners had been engaging in warrantless mass surveillance, using the internet and cellphone data, and driven by fear of terrorism under the sign of ’security’. In this compelling account, surveillance expert David Lyon guides the reader through Snowden’s ongoing disclosures: the technological shifts involved, the steady rise of invisible monitoring of innocent citizens, the collusion of government agencies and for-profit companies and the implications for how we conceive of privacy in a democratic society infused by the lure of big data. Lyon discusses the distinct global reactions to Snowden and shows why some basic issues must be faced: how we frame surveillance, and the place of the human in a digital world. Surveillance after Snowdenis crucial reading for anyone interested in politics, technology and society. David Lyon directs the Surveillance Studies Centre, is a Professor of Sociology, holds a Queen's Research Chair and is cross-appointed as a Professor in the Faculty of Law at Queen's University, Canada